Protocol for a randomised, single-blind, two-arm, parallel-group controlled trial of the efficacy of rhinothermy delivered by nasal high flow therapy in the treatment of the common cold. Issue 6 (19th June 2019) - Bird, Grace; Braithwaite, Irene; Harper, James; McKinstry, Steven; Koorevaar, Iris; Fingleton, James; Semprini, Alex; Dilcher, Meik; Jennings, Lance; Weatherall, Mark; Beasley, Richard
Abstract : Introduction: The common cold is the most common infectious disease affecting humans. It is usually a self-limiting disease; however, the common cold can cause significant morbidity and has a substantial economic impact on society. Human rhinoviruses (HRVs), which cause up to two-thirds of colds, have temperature-dependent replication and most HRV strains replicate optimally at 33°C. Delivery of heated, humidified air to the upper airways has the potential to reduce viral replication, but evidence of the effectiveness of this treatment of the common cold is inconclusive. We plan to test the hypothesis that delivery of humidified air heated to 41°C at high flow, nasal high flow rhinothermy (rNHF), for 2 hours daily for five days is more effective in reducing common cold symptom severity and duration than five days of 'sham' rhinothermy. Methods and analysis: This is a randomised, single-blind, parallel-group trial comparing rNHF to 'sham' rhinothermy in the treatment of common cold. We plan to recruit 170 participants within 48 hours of the onset of symptoms of common cold and randomise them 1:1 to receive one of the two treatments for five days. The study duration is 14 days, which includes clinic visits on the first day of randomisation and four days post-randomisation, and a phone call on the 14th day. Participants will complete daily symptom diaries which include a symptom score, the Modified Jackson Score (MJS). The primary outcome is the MJS after four days. Ethics and dissemination: New Zealand Ethics Registration: 17/STH/174. Results will be published in a peer-reviewed medical journal, presented at academic meetings, and reported to participants. Trial registration number: U1111-1194-4345 and ACTRN12617001340325; Pre-results.